Optimal Integration of Distributed Generation in Distribution System: A Case Study of Sallaghari Feeder from Thimi Switching Station, Bhaktapur, Nepal - Pancha, Basanta; Shrestha, Rajendra; Jha, Ajay Kumar (Journal of the Institute of Engineering, 2020)
The modern power distribution network is constantly being faced with an ever-growing load demand resulting into increased burden and reduced voltage, which leads to find alternative source of energy to meet it. In Nepal, the electricity supply is based on hydropower primarily, which are situated very far from load centers and hence the generated power are to be transmitted through transmission and distributed system. Among the systems, radial distribution system is popular because of low cost and simple design, but it has power quality issues like low voltage profile and higher loss. In response to the problem of increased load demand, efforts have been made to decentralize this infrastructure through the use of distributed generators. However, the improper sizing and placement of DG unit may lead to higher power loss and power instability. The optimization problem of DG unit placement and its capacity determination were performed in this research. The study has been carried out for Thimi-Sallaghari Feeder and this feeder has low voltage profile and higher power loss. The IEEE 33 bus test system was examined as a test case to demonstrate the effectiveness of the proposed approach. The study has been carried out in MATLAB using “Backward and Forward Sweep Method” for load flow analysis and Genetic Algorithm for optimization. The number of DG unit of different size integrated was varied from one to ten. The result of this study showed that the voltage at minimum voltage node, maximum active and reactive loss reduction of Thimi-Sallaghari feeder have been improved by 3.69% (from 0.942 p.u. to 0.976 p.u), 75.88 % and 75.88 % respectively with placement of DG units at three bus locations of total 658.2019 kW and 395.873 kVAR capacity. Likewise, the voltage at minimum voltage node, maximum active and reactive loss of IEEE- 33 bus system have been improved by 6.88 %, 90.11% and 89.9% respectively with placement of DG units of total 2215.488 kW and 1176.059 kVAR at 6 different locations of the network.